Tradisi dan Kepercayaan: Eksplorasi Komunikasi Ritual dalam Merajut Kerukunan Komunitas Bugis Towani Tolotang Sulawesi Selatan, Indonesia - Hadawiah, Hadawiah; Sulaeman, Sulaeman; Ridwan, M.; Norau, Mohamad Rizki (Jurnal Pekommas, 2024)
This research aims to explore the ritual communication experience in knitting the harmony of the Bugis Towani Tolotang community in Amparita Sidenreng Rappang, South Sulawesi, Indonesia. The Bugis Towani Tolotang community has various local traditions and beliefs regarding social care, kinship, diversity, togetherness and equality as solidarity identity which is realized in building harmonious relationships. Data was obtained qualitatively through several informal conversational interviews through ritual communication (Tallotte, 2018) based on ritual theory (Turner 1962, 1969), and phenomenology (Schutz, 1972). The article focuses on the experience of the Bugis Towani Tolotang community, which is a group of communities that believe in worshiping God Dewata Seuwae. Bugis Towani Tolotang constructs ritual communication as a local tradition with its symbols and is considered to have meaning, including the meaning of offerings, requests and hopes. This meaning results from the communication process of subjective interpretation of the rituals mutual cooperation rituals, marriage, sipulung, mappenre inanre, and tudang sipulung. The article contributes to realize harmonious community relations through the discussion of finding the meaning of Bugis Towani Tolotang rituals in the hope of living together peacefully in kinship ties. Strengthening solidarity is essential as it forms bonds of kinship and togetherness. This contribution offers opportunities for traditional accommodation and ways of forming kinship bonds.